Comparison of maximal lactate steady state with anaerobic threshold determined by various methods based on graded exercise test with 3-minute stages in elite cyclists - Kamila Płoszczyca; Dominik Jazic; Zofia Piotrowicz; Małgorzata Chalimoniuk; Józef Langfort; Miłosz Czuba (BMC, 2020)
Abstract Background The maximal lactate steady state (MLSS) is defined as the highest workload that can be maintained for a longer period of time without continued blood lactate (LA) accumulation. MLSS is one of the physiological indicators of aerobic performance. However, determination of MLSS requires the performance of a series of constant-intensity tests during multiple laboratory visits. Therefore, attempts are made to determine MLSS indirectly by means of anaerobic threshold (AT) evaluated during a single graded exercise test (GXT) until volitional exhaustion. The aim of our study was to verify whether AT determined by maximal deviation (Dmax), modified maximal deviation (ModDmax), baseline LA concentration + 1 mmol/l (+ 1 mmol/l), individual anaerobic threshold (IAT), onset of blood lactate accumulation (OBLA4mmol/l) and V-slope methods based on GXT with 3-min stages provide valid estimates of MLSS in elite cyclists. Methods Twelve elite male cyclists (71.3 ± 3.6 ml/kg/min) completed GXT (the increase by 40 W every 3 min) to establish the AT (by Dmax, ModDmax, + 1 mmol/l, IAT, OBLA4mmol/l and V-slope methods). Next, a series of 30-min constant-load tests to determine MLSS was performed. Agreement between the MLSS and workload (WR) at AT was evaluated using the Bland-Altman method. Results The analysis revealed a very high (rs > 0.90, p < 0.001) correlation between WRMLSS and WRDmax and WRIAT. The other AT methods were highly (rs > 0.70) correlated with MLSS except for OBLA4mmol/l (rs = 0.67). The Bland-Altman analysis revealed the highest agreement with MLSS for the Dmax, IAT and + 1 mmol/l methods. Mean difference between WRMLSS and WRDmax, WRIAT and WR+1mmol/l was 1.7 ± 3.9 W, 4.3 ± 7.9 W and 6.7 ± 17.2 W, respectively. Furthermore, the WRDmax and WRIAT had the lowest limits of agreement with the WRMLSS. The ModDmax and OBLA4mmol/l methods overestimated MLSS by 31.7 ± 18.5 W and 43.3 ± 17.8 W, respectively. The V-slope method underestimated MLSS by 36.2 ± 10.9 W. Conclusions The AT determined by Dmax and IAT methods based on the cycling GXT with 3-min stages provides a high agreement with the MLSS in elite cyclists. Despite the high correlation with MLSS and low mean difference, the AT determined by + 1 mmol/l method may highly overestimate or underestimate MLSS in individual subjects. The individual MLSS cannot be properly estimated by V-slope, ModDmax and OBLA4mmol/l methods.